Exploring the pore fluid origin and methane-derived authigenic carbonate properties in response to changes in the methane flux at the southern Ulleung Basin, South Korea - Kim, Ji-Hoon; Park, Myong-Ho; Ryu, Jong-Sik; Jang, Kwangchul; Choi, Jiyoung; Park, Sanghee; Song, Yungoo; Yi, Bo-Yeon; Joo, Young Ji; Kim, Tae-Hoon; Hur, Jin (Frontiers in Marine Science, 2024)
We investigated the geochemistry of gas, pore fluid, and methane-derived authigenic carbonate (MDAC) from four sites in the southern Ulleung Basin, South Korea. In contrast to Sites 16GH-P1 and 16GH-P5, Sites 16GH-P3, and 16GH-P4 are characterized by acoustic chimney structures associated with gas flux. The composition of gas and isotopic signatures of methane (CH4) (C1/C2+ > 300, δ13CCH4 < -60‰, δDCH4 ≤ -190‰) indicate microbial source CH4 at all sites. The upward migration of CH4 can affect the chemical and isotopic properties of pore fluid and gas-related byproducts (e.g., gas hydrate (GH) and MDAC) within the shallow sediments including the current sulfate-methane transition (SMT) (< 5 meters below seafloor). Although no GH was found, elevated Cl- concentrations (maximum = 609 mM) with low δD and δ18O values in Site 16GH-P4 pore fluids delineate the influence of massive GH formation in deeper sediment. In contrast, relatively constant Cl-, δD, and δ18O values in fluids from Sites 16GH-P1, 16GH-P3, and 16GH-P5 indicate a predominant origin from seawater. Pore fluids also exhibit higher concentrations of H4SiO4, B, Mg2+, and K+, along with increasing alkalinity compared to seawater. These observations suggest that marine silicate weathering alters fluid chemistry within the sediment, affecting element and carbon cycles. High alkalinity (up to 60 mM) and Mg2+/Ca2+ ratios (> 6) alongside decreasing Ca2+ and Sr2+ concentrations imply carbonate precipitation. MDACs with diverse morphologies, mainly composed of aragonite and magnesian calcite, and characterized by low carbon isotopic values (δ13CMDAC < -31.3‰), were found at Sites 16GH-P3 and 16GH-P4. Interestingly, δ13CMDAC values at Site 16GH-P3 are clearly differentiated above and below the current SMT. High δ13CMDAC values above the SMT (> -34.3‰) suggest the combined influence of seawater and CH4 migrating upward on MDAC precipitation, whereas low δ13CMDAC values below it (< -41.6‰) indicate a predominant impact of CH4 on MDAC formation. Additionally, the vertical variation of δ18OMDAC values at Site 16GH-P4, compared to the theoretical values, reflects an association with GH dissociation and formation. Our findings improve the understanding of fluid, gas, and MDAC geochemistry in continental margin cold seeps, providing insights into global carbon and element cycles.